Soil drying cycles in the succulent Karoo : different rooting systems and water uptake - Currie, Gwen (Department of Biological Sciences, 2017)
In the semi-arid Succulent Karoo water is one of the most limiting resources, and plants that survive in the area require competitive water-use strategies suited to long periods of drought. Over the years much emphasis has been put on mechanisms that allow for the competitive success of water-use strategies, and root structure features as an important attribute. This study investigated soil drying cycles in the semiarid Succulent Karoo. It measured the rates at which soil water was depleted at two different depths in five different microhabitats, and investigated whether these are related to different rooting systems. Three prevalent plant species in the region were used, namely Leipoldtia schultzei of the Mesembryanthemaceae, Tripteris sinuata of the Asteraceae, and Galenia africana of the Aizoaceae, all of which have their roots in the upper 20cm of soil. However, Leipoldtia's roots are concentrated in the top 5cm of soil, while the other two species root mainly at depths between 10 and 20cm. This vertical separation of roots provided the opportunity to relate soil water depletion at two different depths (0-10cm and 10-20cm) to the different rooting strategies, and explore what this means in te1ms of compatibility between close neighbours and seedling establishment under adult plants. The shallow-rooting Leipoldtia showed the highest rates of soil moisture depletion in both the shallow and deeper soil zones, and is therefore a strong competitor for water and probably an undesirable neighbour. Soils at both depths below Tripteris plants maintained the highest moisture content over the 2-week period of sampling, suggesting it to be favourable site for seedling establishment. Galenia showed intermediate soil-drying effects in the upper 0-10cm, but high rates of moisture depletion at 1 0-20cm below the surface, suggesting that it may be a suitable neighbour for shallow-rooting species but not for other deeper rooting species. Additionally, the two sampling methods - electronic probe readings and gravimetric analysis - were examined. The two methods correlated fairly well to each other (R2 = 0.759 ± 0.002), although the probe readings were consistently higher and showed greater variation (probe SD = 2.8 as opposed to gravimetric SD = 1.2)